There are no Foodstuffs in Grocery Stores, Everything is Very Difficult to Obtain: Women’s Everyday Life in the Provincial Soviet City in the 1950-1960s - Natalia L. Pushkareva; Irina V. Bogdashina (RUDN Journal of Russian History)
The authors have explored alimentary practices (obtaining, preparing, cooking, consuming foodstuffs) in the context of gender relations, social history of women and everyday life of women in non-capital cities of the USSR in the late 1950s - early 1960s. The main sources of their work are: personal documents (unpublished diaries and memoirs), materials from recipe books that were in almost every home at that time, information from periodicals (magazines), archival materials from the funds of the State Archives of the Volgograd Region and the Center for Documentation of the Contemporary History of the Volgograd Region, and specific office documents - reports of inspections of district committees of people's control and confirming facts of abuse in the sphere of public catering. The main source is unstructured oral biographical stories or “women's oral story,” which preserved an emotional assessment of the difficulties experienced at that time. In the anthropology of Soviet everyday life, the gender aspect plays an especially significant role, since the ordinary and inconspicuous things in everyday life are better captured and preserved by women's memory; women's everyday life differed significantly from men's due to the greater burden of household chores. The authors conclude that despite the social policy of the Soviet state aimed at freeing women from household chores, the patriarchal idea of the role of women in the family turned out to be stable phenomena and can be traced throughout the Soviet period, including the “thaw.” Moreover, across the period there was the formation of a special type of Soviet gastronomic culture, simplified in terms of recipes, a form simplicity which provided time and energy for women's activities outside the home.